Speed limit sign board detection and extraction of digits in different weather conditions - Rahman, Khan Hafizur Rahman; Alam, Md. Zubair (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.